Power System Stability Enhancement and Improvement of LVRT Capability of a DFIG Based Wind Power System by Using SMES and SFCL - Anju Murukeshan; R. Rajasekaran (Institute of Advanced Engineering and Science, 2013)
This paper proposes a exhaustive study about the performance analysis of Doubly Fed Induction (DFIG) under abnormal condition. Now a days, majority of power network countenance the problem of over current and grid connectivity issues. SFCL (Superconducting Fault Current Limiter), which have the competence to limit the fault current and protect the equipments from damage. SMES (Superconducting Magnetic Energy Storage) is mainly used to compensate both real and reactive power variations, thus power quality can be enhanced. Co-ordinated operation of SFCL - SMES thus used to enhance the power system stability and improve the LVRT (Low Voltage Ride Through) capability of wind power generation systems. LVRT capability of wind turbine is refers to the ability of wind power system to conquer the voltage variations if there is any unwanted conditions. Here DFIG based wind turbine plant is used for consideration, because it will provide smoothened power output nearly double than a conventional generator. And it have more simple and rugged construction also. Design of DFIG based wind power generation systems under fault condition with the help of SMES and SFCL is analysed by means of MATLAB/SIMULINK block set.DOI:http://dx.doi.org/10.11591/ijece.v3i5.3383